Development and early validation of questionnaires to assess system level factors affecting male partners' attendance at childbirth in LMICs - Thierry Claudien Uhawenimana; Nicola M. Gray; Heather Whitford; Alison McFadden (BMC, 2023)
Abstract Background There is evidence that a woman who receives continuous labour support from a chosen companion can have shorter labour duration, is more likely to give birth without medical interventions, and report a satisfying childbirth experience. These outcomes result from the beneficial effects of emotional and practical support from the woman's chosen companion, and care provided by health providers. When a woman's chosen companion is her male partner, in addition to the above benefits, his presence can promote his bonding with the baby, and shared parenthood. However, there may be healthcare system barriers, including organisational, management and individual (staff) factors, that inhibit or restrict women's choice of companion. There are currently no suitable survey tools that can be used to assess the system level factors affecting the implementation of male partners' attendance at childbirth in low- and middle- income countries (LMICs). Methods We designed two questionnaires to help to address that gap: the Male Partners' Attendance at Childbirth-Questionnaire for Heads of Maternity Units (MPAC-QHMUs); and the Male Partners' Attendance at Childbirth-Questionnaire for Maternity Staff (MPAC-QMS). We carried out an extensive review to generate initial items of the two questionnaires. We assessed the content and face validity of the two questionnaires in a three-round modified Delphi study. Results The Male Partners' Attendance at Childbirth-Questionnaire for Heads of Maternity Units (MPAC-QHMUs) focused on organisational and management factors. The Male Partners' Attendance at Childbirth-Questionnaire of Maternity Staff (MPAC-QMS) focused on individual staff factors. The final MPAC-QHMUs and MPAC-QMS included items which garnered over 80% content relevance according to the experts' rating. After all three consensus rounds of the Delphi study, 43 items were retained for the MPAC-QHMUs and 61 items were retained for the MPAC-QMS. Conclusions The MPAC-QHMUs and the MPAC-QMS may help understanding of barriers affecting male partners' attendance at childbirth in LMICs in order to devise implementation strategies to enable wider availability and to maximize women's choices during labour and childbirth. The MPAC-QHMUs and the MPAC-QMS as newly-developed questionnaires require further validation of their acceptability and feasibility in different cultural contexts, and languages.